Aplicabilidade das técnicas de determinação de tamanho de partículas em sistemas de tratamento de água e esgoto sanitário - Santos, Hélio Rodrigues Dos (2004)
The improvement of water and wastewater treatment systems has been limited by the little knowledge of phenomena that take place inside the units and by the use of non-specific parameters (e.g. BOD, COD etc.) in monitoring and controlling of treatment processes and operations. On the other hand, phenomena such as mass transfer, adsorption, diffusion and biochemical reaction are all influenced by particle size distribution, in a way that the use of particle size measurement can aid in choosing and improving treatment technology and in adoption of appropriate operational procedures. In this article, the main particle size measurement techniques are presented, as well as the potential benefits of its use in research and in the improvement of design and operational routines for water and wastewater treatment systems.